Manajemen pembelajaran siswa dengan Autism Spectrum Disorder (ASD) di SLB Samara Bunda Yogyakarta - Subarji, Subarji; Mulyoto, Mulyoto (Literal: Disability Studies Journal, 2024)
This study aims to determine the implementation of learning management students who have autistic disorders that include planning, organizing, implementing and evaluating for children with autistic disorders in Samara Bunda SLB Yogyakarta. Supporting factors and inhibitors in the implementation of learning for students who experience autistic disorders in Samara Bunda SLB Yogyakarta. The results of the ability of students who experience autism disorders after getting learning at Samara Bunda Yogyakarta SLB, this study uses a qualitative approach, the data sources in this study include the principal, vice principal of the affairs of Curriculum, Studentism, Advice and Infrastructure, class teacher, school committee, people old students, and documents, the main instrument in this study is the researcher. Learning management for students with autistic disorders consists of 1). Learning planning, 2). Organizing learning, 3). Implementation of learning, 4). Evaluation of learning. Students' ability as a result of participating in learning programs at Samara Bunda SLB is that students become emotionally stable, independent, confident, concentrated, child behavior becomes more controlled, social communication skills are increased, skilled and capable. Factors that support the learning of students with autistic disorders in Samara Bunda SLB are good and directed student abilities, good cooperation between the school and parents / guardians, good cooperation between schools, the government, stakeholders and observers of education in students with autism disorders , availability of facilities and infrastructure, adequate funding, and experts. The inhibiting factors in achieving learning goals are the students' initial abilities that have not been good, not directed, and behaviors that cannot be controlled, the absence of continuity between teachers and parents